The opaque mineralogy of metasedimentary rocks of the Meguma Group, Beaverbank-Rawdon area, Nova Scotia - Haysom, S. J.; Horne, R. J.; Pe-Piper, G. (Atlantic Geoscience, 1997)
Opaque mineralogy of a representative cross-section of deformed and metamorphosed turbiditic slate and metasandstone of the Meguma Group has been investigated optically and by electron microprobe. A strong stratigraphic control over the presence and abundance of certain opaque minerals is recognized, which may prove useful for environmental evaluation such as acid drainage potential. Abundant pyrite and pyrrhotite in the lower Halifax Formation reflect concentration of early diagenetic pyrite resulting from the reduction of seawater sulphate under anoxic conditions. Magnetite is restricted to the Goldenville Formation. Dmcnitc and rutile occur throughout the succession, and minor chalcopyrite, arsenopyrite, covellite, hematite and glaucodot were also noted. Pyrrhotite and ilmenitc, as well as spcssartine, chlorite and chloritoid porphyroblasts, developed during pro-grade metamorphism before and/or during cleavage formation, which also resulted in removal of early diagenetic pyrite. Later pyrite formed by replacement or immobilization of pyrrhotite during retrograde metamorphism. Colloform pyrite, arsenopyrite and chalcopyrite are the youngest mineral phases. R&3xC9;SUMÉ On a étudie la structure méniralogique opaque d’un échantillon représentatif de métagrès et d’ardoisc turbiditique déformés et mélamorphisés du groupe de Meguma, optiquement ainsi qu’è l’aide d’une microsonde électronique. On a ainsi reconnu un contrdle stratigraphique prononcé sur la présence et l’abondance de certains minéraux opaques, ce qui pourrait s’avérer utile pour une évaluation environnementale, comme celle du potentiel de drainage acide. Les quantités abondantes de pyrite et de pyrrhotine dans la partie inférieure de la Formation d’Halifax témoignent d’une concentration de pyrite diagcénétique précoce provenant de la réduction du sulfate d’eau salié dans des conditions anoxiques. La magnétite se limite à la Formation de Goldenville. On relève la présence d’ilménite et de rutile partout dans la succession, en plus de petites quantités de chalcopyrite, d’arsénopyrite, de covellite, d’hématitc et de glaucodot. La pyrrhotine et l’ilménite, tout comme la spcssartine, la chlorite et les porphyroblastes chloritoldes, sont apparus au cours d’un métamorphisme progradc avant ou pendant la formation du clivage, qui a provoqué en plus un retrait de la pyrite diagénétique précoce. La pyrite ultérieure s’est formic par remplacement ou remobilisation de la pyrrhotine au cours d’un rétrométamorphisme. La pyrite colloforme, l’arsénopyrite et la chalcopyrite représentent les phases minérales les plus récentes. [Traduit par la rédaction]